Effect of Pressure and Syngas Composition on Direct Synthesis of Dimethyl Ether using Dual Bed Catalyst - Aisyah Ardy; Jenny Rizkiana; Melia Laniwati Gunawan; Herri Susanto (ASEAN Journal of Chemical Engineering, 2019)
National General Energy Plan of Indonesia 2017 (RUEN 2017) stated that dimethyl ether (DME) is appointed as a blending of LPG to reduce LPG imports. DME can be made with two reaction pathways, namely direct synthesis and indirect synthesis. The objective of this study was to determine the effect of pressure and syngas composition on the direct synthesis of DME using dual fixed bed catalyst. The research was carried out with two types of catalyst: M-xxx as a commercial catalyst for methanol synthesis and γ-Al2O3 as catalyst for dehydration of methanol to DME. The later was prepared in our Laboratory of Chemical Reaction Engineering and Catalysis, ITB. The dual catalyst experiment was carried out at 5 and 7 bars, and a fixed temperature of 240oC. The mass ratio of the M-xxx to γ-Al2O3, so-called M/D ratios, were varied from 1/9 to 9/1. Two type of syngas were used, i.e. SA containing only H2 and CO with a SN of 2,3 and SB containing 4% CO2 with SN of 1,8. The dual bed with a M/D ratio of 1/4 gave a CO conversion up to 62% at 5 bars and 240oC (SA). As pressure increased, the conversion of CO and H2 increases to 85% and 83% at 7 bar and 240oC (SA). The presence of CO2 (SB) decreases catalyst activity, as indicated by the decrease in conversion of CO and H2 to 56% and 54%, at 7 bar and 240oC.